SOSIAL EKONOMI KOMUNITAS PEMULUNG DI TPA LUBUK MINTURUN (Economic Education Faculty of Economics and Business Universitas PGRI Sumatera Barat, 2012)
This research aims to expose the social economic of Pemulung community in TPA Lubuk Minturun. This research applies qualitative research. The informan of this research are Pemulung in TPA Air Dingin Kelurahan Balai Gadang, Kecamatan Koto Tangah Kota Padang by using snowball sampling. The datas are gathered by observing, interviewing, and documenting. In purpose of keeping the data authenticity, it is needed the explanations from the credible information (credible and realiable) from the selected items (Mestika Zed, 1999). The research show that the low level of education of Pemulung does not affect toward their income in TPA Air Dingin because what they do, does not need certain skills and education. Their strategies to gather things are to search them form early morning and they involve all of family members in term of “Maraok”. While in marketing strategy, they sell the thing they have got to the collector (Lapak owner) who wants to buy more expensive or they sell whenever the price is higher. Pemulung in TPA Air Dingin have never got direct financial security from the government of Padang, so that it affects to the structural poverty. The way of live they have cause such a structural poverty. They are used to be relax and feel comfort with their work system. Pemulung in TPA Air Dingin do not want to change the system that they have made, so that still live in the circle of cultural poverty.